Digital Dakwah Communication Strategy: Case Study Gus Iqdam Reaching Tuesday Night At Markas Sabilu Taubah, Karanggayam Srengat Blitar Village: Strategi Komunikasi Dakwah Digital: Studi Kasus Pengajian Malam Selasa Gus Iqdam Di Markas Sabilu Taubah Desa Karanggayam Srengat Blitar - Zuhro, Fathimatuz; Rohmah Hidayati; Faishol, Muhammad (QULUBANA: Jurnal Manajemen Dakwah, 2024)
Thus, the Prophet (peace and blessings of Allah be upon him) said: “Behold, the prophet Muhammad (salla Allahu alihi wa sallam) is a prophet of all sins. The role of mass media facilitates the delivery of messages that were once oral to oral becomes unlimited distance and time. New media is not only done for negative things. New media can also play a role as a positive media especially in spreading good through publicity. The most widely used media in modern times is social media. Social media is the communication media that almost all the world's societies use. The aim of this research is nothing more than to know and interpret in depth the communication strategy of Gus Iqdam in giving an explanation to Mad’u in the digital age, because this modern age is encouraging to analyze the content of Guss Iqdams communications spread on social media that surely affects its audience.